Translational PK/PD and model‐informed development of JNJ‐67842125, a Fab reversal agent for JNJ‐64179375, a long‐acting thrombin inhibitor. (29th June 2021) - Ayyar, Vivaswath S.; Jaiprasart, Pharavee; Geist, Brian; Huang Devine, Zheng; Case, Martin; Hazra, Anasuya; Hsu, Chyi‐Hung; Chintala, Madhu; Wang, Weirong
Abstract : Background and Purpose: Antigen‐binding fragment (Fab ) reversal agents were developed to reverse, in bleeding emergency, the long‐acting anticoagulant effect of JNJ‐64179375 (JNJ‐9375), a monoclonal antibody that binds exosite‐1 on thrombin. Experimental Approach: The pharmacokinetic and pharmacodynamic (PK/PD) activities of three reversal agents of varying in vitro binding affinities to JNJ‐9375 were characterised in cynomolgus monkeys. The time course of JNJ‐9375 anticoagulant activity and reversal effects of each agent were evaluated. A mechanism‐based PK/PD model, which integrated free serum concentrations of reversal agent, total and free serum concentrations of JNJ‐9375, and thrombin time, was developed to quantitatively relate JNJ‐9375 neutralisation to reversal of induced thrombin time prolongation. Model‐based allometric scale‐up of the lead reversal agent and the PK/PD relationship of JNJ‐9375 in healthy volunteers were utilised to predict clinical dosing regimens. Key Results: Lowering of free JNJ‐9375 by the reversal agents corresponded with reversal of thrombin time prolongation. Total JNJ‐9375 displayed typical mAb clearance at 2.75 ml·day −1 ·kg −1, whereas reversal agents cleared faster between 1400 and 2400 ml·day −1 ·kg −1 . The model‐estimated in vivo KD values for JNJ‐9375 reversal agents were 9 nM (ICHB‐256), 0.4 nM (ICHB‐281) and 13.7 pM (ICHB‐164), in rank‐ordered agreement of their KD values determined in vitro . The three reversal agents exhibited different neutralisation characteristics in vivo, governed primarily by their binding kinetics to JNJ‐9375. The model predicted a priori free JNJ‐9375 kinetics after dosing ICHB‐164 (JNJ‐67842125) and JNJ‐9375 under a different regimen. Conclusion and Implications: The results enabled selection of JNJ‐67842125 as the reversal agent for JNJ‐9375.